Ripensare ‘la società dell’azione’ e ricominciare a ‘guardare il cielo’: la montagna come ‘controambiente del sublime’ in una inedita partitura urbana - Decandia, Lidia (Scienze del Territorio, 2016)
Recalled the role that places of silence have had during other crisis in the history of humanity, the paper enquires into the role that mountains and inland areas, ‘discarded’ by modernity, might have today, when even our development model looks weary, in reconfiguring the very idea of city. Analysing many clues revealing how swarms of nomads, in flight from the consolidated city, are shifting towards the mountains in search of new places, capable of offering a geography alternative to the high-speed, dense, noisy metropolitan spaces, the author argues that, as in remote times, such ‘discarded’ territories might indeed acquire a new meaning within a wider-ranging territorial dimension. And turn into cornerstones to start from in order to create a new city apt to return space to the deepest dimensions of humanity. A city no longer conceived as a confined and bounded agglomeration, but as a complex musical score in which, alternating full and empty spaces, density and interludes, adagios and fast tempos, deserted places and high-intensity nodes, silence too could finally be heard.